PELATIHAN PENGGUNAAN MEDIA TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) DI SEKOLAH DASAR - Sri Mulyani; Nurratri Kurnia Sari; Sri Mulyati; Y Sugiarto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Training in the use of Media Technological Pedagogical Content Knowledge (TPACK) in SD Negeri 1 Wonoboyo, a significant change in the understanding and practice of using technology in learning is seen. Before the training, the majority of teachers relied on PowerPoint as the main tool in learning, but after participating in the PPG program, some teachers began to adopt TPACK media such as Lifeworksheet, Kahoot. The process of designing learning media based on TPACK is also not optimal, especially in ensuring the effectiveness of learning during the pandemic. During the training, teachers were given an in-depth understanding of the TPACK concept, including the role of each component in the learning context. They were also given direct demonstrations on how to use various media in learning as well as being involved in practicum and training. Group discussions and constructive feedback also help them improve their skills in integrating technology learning. In addition, teachers are also given the task of planning the use of technology in daily learning in the classroom. The evaluation results show an increase in the creativity of teachers in presenting TPACK learning materials.